Unidentified Verbal Objects - Esa Kirkkopelto (Performance Philosophy)
This article considers how artistically performative practices, especially the scenic embodiment of words, problematizes our accustomed understanding of language, both in a philosophical and an everyday sense. In classical phenomenology à la Heidegger or Merleau-Ponty, language is considered a medium of the process of appearing or expression. As I try to sustain, language should instead be understood as the medium of appearing; not as the primary medium, nor as a medium among others, but as an intrinsic aspect of all appearing, no matter what its medium, user, or level of development. This conclusion, if it holds, leads towards an expanded idea of language where being linguistic and being or having a body coincide. The idea is sustained by evidence rising out of consideration of the basic corporeal operations of a scenic performer as they try to embody their textual material performatively. Through this idea, the article seeks a reconciliation to a debate between post-structuralist and post-humanist thought regarding the role and scope of language in knowledge formation.